Acute Myocardial Infarction in Severe Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Surviving Case - Cempakadewi, Ade Ajeng; Puspita Sari, Putu Ayu Diah; Budiana, I Putu Gede (Jurnal Respirologi Indonesia, 2024)
Background: COPD is characterized by chronic respiratory symptoms with progressive, irreversible structural abnormalities and impaired lung function. Previously, COPD was known as a condition that only affected the airways and lungs, but recent studies have revealed the incidence of cardiovascular disease in this population as the prevalence increased.Case: A 68-year-old male came to the emergency room fully conscious, complaining of shortness of breath since the afternoon. A physical examination detected tachypnea, desaturation of oxygen, and additional breath sounds in both lungs. Blood gas analysis with the result of respiratory acidosis supported the diagnosis of AECOPD (acute exacerbations of chronic obstructive pulmonary disease), impending type II respiratory failure, cor-pulmonale. During the treatment in the intensive unit, the physicians recognized deteriorating conditions as unconsciousness, unstable vital signs, and ST-T segment changes on the ECG with an elevated cardiac marker. Other medications (antiplatelet, LMWH, and statin) were given immediately. The patient’s condition improved. On the ninth day of the treatments, the patient was discharged home.Discussion: Acute exacerbations of COPD have a higher risk of developing ischemic heart disease with varying underlying mechanisms (atherosclerosis process and oxygen supply-demand imbalance). Understanding the numerous pathways that contribute to AMI (acute myocardial infarction) in COPD will help physicians determine the therapy.Conclusion: Based on this case, the ECG and cardiac enzymes warrant immediate evaluation, as must symptoms, vital signs, clinical findings, and other changes. Delays in case finding and treatment can worsen the prognosis.